A genome sequence resource for the genus Passiflora, the genome of the wild diploid species Passiflora organensis. Issue 3 (23rd July 2021) - Costa, Zirlane Portugal; Varani, Alessandro Mello; Cauz‐Santos, Luiz Augusto; Sader, Mariela Analía; Giopatto, Helena Augusto; Zirpoli, Bruna; Callot, Caroline; Cauet, Stephane; Marande, Willian; Souza Cardoso, Jessica Luana; Pinheiro, Daniel Guariz; Kitajima, João Paulo; et al.
Abstract: The genus Passiflora comprises a large group of plants popularly known as passionfruit, much appreciated for their exotic flowers and edible fruits. The species (∼500) are morphologically variable (e.g., growth habit, size, and color of flowers) and are adapted to distinct tropical ecosystems. In this study, we generated the genome of the wild diploid species Passiflora organensis Gardner by adopting a hybrid assembly approach. Passiflora organensis has a small genome of 259 Mbp and a heterozygosity rate of 81%, consistent with its reproductive system. Most of the genome sequences could be integrated into its chromosomes with cytogenomic markers (satellite DNA) as references. The repeated sequences accounted for 58.55% of the total DNA analyzed, and the Tekay lineage was the prevalent retrotransposon. In total, 25, 327 coding genes were predicted. Passiflora organensis retains 5, 609 singletons and 15, 671 gene families. We focused on the genes potentially involved in the locus determining self‐incompatibility and the MADS‐box gene family, allowing us to infer expansions and contractions within specific subfamilies. Finally, we recovered the organellar DNA. Structural rearrangements and two mitoviruses, besides relics of other mobile elements, were found in the chloroplast and mt‐DNA molecules, respectively. This study presents the first draft genome assembly of a wild Passiflora species, providing a valuable sequence resource for genomic and evolutionary studies on the genus, and support for breeding cropped passionfruit species. Core Ideas: Passiflora organensis has a small genome of 259 Mbp. We estimate that the repetitive content of the P. organensis genome is approximately 59%. We predicted 25, 327 protein‐coding genes and genes involved in self‐incompatibility. Organelle DNAs were recovered; two mitoviruses and relics of mobile elements occurred in mtDNA. This study provides a promising resource for comparative genomic analysis of Passiflora .